Prevenção de violência e promoção de relações de intimidade saudáveis na adolescência: análise de um programa de intervenção - Souza, Marina Soares (2020)
During adolescence, interpersonal relationships receive greater value; the family space expands to build new interactions and relationships. In general, the adolescent does not present great rates of illness or mortality in comparison with other phases of human life; however, they may be vulnerable to phenomena such as violence. In recent years, studies have focused on intimate partner violence among adolescents. An approach is made for some factors, such as the early establishment of unhealthy intimate relationships in people's lives and, in this field, as a strategic area for the prevention of intimate partner violence and the promotion of healthy intimate relationships. The objective of this study was to evaluate the effects of a multicomponent intervention program that aims to aware adolescents about intimate partner violence, enabling them to build healthy relationships. A quasi-experimental study, with evaluation of 8th and 9th graders about intimate partner violence knowledge and social skills for building healthy relationships before (n= 105) and after (n= 88) an intervention. This intervention was based on the ecological model of understanding violence and was carried out in a public school in São Carlos-SP with adolescents, parents and teachers. The adolescents answered to the sociodemographic questionnaire, to the intimate partner violence knowledge in the reduced version and to the social skills questionnaires. Descriptive and inferential statistics were used, being applied chi-square and Wilcoxon tests. The average age was 13.9 years, being 48.6% of female adolescents, 78.1% had religion, 75.2% already had some type of intimate relationship and of these, 6.7% were recognized as victims and/or perpetrators of some type of violence. The groups did not present significant differences in the comparison of the collection times. However, some specific items in the questionnaires had important p-value ranging from .037 to <.001. The p value .037 refers to the variable "Violence can continue after the dating ends" of the intimate partner violence knowledge questionnaire. While the variables "I participate in school activities such as sports teams and guilds", " I ignore classmates who are clowning" and "I receive criticism from my parents without getting upset" of the social skills questionnaire also presented significant p value with .03 for the first variable and .036 for the other variables indicated. Still on the last questionnaire, although it presented non-significant total values, all variables, individually, indicated p value <.001. It is concluded that preventive programs about intimate partners violence that promote healthy relationships still need further practical study, considering tools and selected strategies for the interventions best suited to the participants' own needs.